Psychological effects of Social Media on Real Life - Andi Semma (Da'wa Faculty of Islamic State University Salatiga, 2022)
Social media nowadays is part of our daily lives. A social media celebrity is used as a trend setter. In this research, we focused on finding the both favorable and adverse effects of social media on real life. The systematic review is used to find these studies’ purposes. We looked for journal articles published between 2017 and 2022. that studied the effect of social media on real life. We focused on empirical studies, positive impacts and its negative impacts’ countermeasures. After that, we analyze and examine what Indonesia currently has in technology and human resources to determine the readiness to adopt the relevant solutions. The result of This research aims to give an overview. of empirical studies of the both favorable and adverse effects of social media and their countermeasures.